Computational analysis of reinforced concrete slabs subjected to impact loads - Mokhatar, Shahrul Niza; Abdullah, Redzuan (Penerbit UTHM, 2011)
Nowadays, the numerical models for the impact load assessment are starting to become more accurate and reliable. Combined with modern computer hardware, the computational time for such an assessment has been reduced to a satisfactory level. In this study, an attempt has been made to present the simulation technique and examine the accuracy of modern software with regards to assessing the response of reinforced concrete slabs subjected to impact loading near the ultimate load ranges. The response such as time-impact force graph, damage wave propagation, effectiveness of mesh density, effect of projectile size and final crack pattern are verified against existing experimental results. It is shown that the present general purpose Finite Element Analysis (FEA) is able to simulate and predict the impact behavior of structural systems satisfactorily.